Toxicity and DNA methylation changes induced by perfluorooctane sulfonate (PFOS) in sea urchin Glyptocidaris crenularis. (June 2015) - Ding, Guanghui; Wang, Luyan; Zhang, Jing; Wei, Yuanyuan; Wei, Lie; Li, Yang; Shao, Mihua; Xiong, Deqi
Highlights: Sea urchins dropped spines and lowered down movement and feeding after exposure. PFOS exposure changed SOD and CAT activities. PFOS increased DNA methylation polymorphism, methylation and demethylation rates. The demethylation rate was lower than the corresponding methylation rate. Abstract: Perfluorooctane sulfonate (PFOS) is an ubiquitous persistent organic pollutant, which can be bioaccumulated and cause adverse effects on organisms. However, there is very limited information about the toxic effects of PFOS to marine organisms and its mechanisms. Therefore, in the present study, adult sea urchins Glyptocidaris crenularis were exposed to PFOS for 21 d, followed by a 7-d depuration period, in order to investigate the toxicity of PFOS to sea urchin and its potential epigenetic mechanisms. Sea urchins dropped spines, and lowered down the motor ability and feeding ability after the PFOS exposure. Superoxide dismutase activities in supernatant of coelomic fluid of sea urchin increased firstly and then dropped down, while the change of the catalase activity took an opposite trend during the exposure period. They both approached to the corresponding activity of the control after the depuration period. The DNA methylation polymorphism, methylation rate and demethylation rate in sea urchin gonad all increased following the prolonged exposure time, and then decreased after the depuration period. The demethylation rates were lower than the corresponding methylation rates, therefore methylation events were dominant during the whole experimental period. This might suggest that sea urchin have strong self-protection mechanisms and can survive from the PFOS exposure presented in this study. Further efforts are needed to more precisely investigate the DNA methylation effects of PFOS and the self-protection mechanism of sea urchin.